Les destins divergents des régionalismes flamands et francophones : une perspective historique - Geoffrey Pion; Gilles Van Hamme (EchoGéo)
The tensions between French-speaking and Dutch-speaking communities in Belgium about the regionalization of federal competences are not new and have to be understood in the long history of regionalism. This article tells the history and the geography of regional waves in Belgium. We will in particular show how these successive regionalist fevers have progressively reshaped the Belgian Central State into a federal State where regions gain in competences over the time. The main hypothesis is that regionalist parties have gone through temporary electoral successes (1919-21, 1936, 1965-77, 2009-?), followed by long period of decline as soon as the regionalist claims of the opinion were satisfied. The next wave of regionalism relies thus on the new claims to deepen the regionalisation of the Belgian State. In this framework, we will insist on the growing support for regionalist parties in the Flemish part of the country since the eighties, in contrast with the quasi absence of Walloon regionalist parties in the recent years. We also show that the geography of regionalist parties have considerably evolved over the time, with the exception of Antwerp which has remained at the heart of most Flemish regionalist parties.